1140 Effect of a Pilot Intervention on Setting Up Long-Term Mechanism of Neonatal Resuscitation Training in 4 Counties in China. (October 2012) - Xu, T; Jin, X; Wang, H; Gong, L; Zheng, X; Yu, G; Xu, G; Zhang, P
Abstract : Background and Aims: Neonatal mortality is the leading cause of under-5 child deaths in China. The aim was to evaluate the effect of a pilot intervention on setting up long-term mechanism of neonatal resuscitation training in 4 counties in China. Methods: A neonatal resuscitation leading group was set up within each county level hospital to lead the in-hospital training, department coordination, resuscitation practices and cases audit. A random control survey was conducted in the intervention counties and 4 randomly selected control counties to evaluate the impact of the intervention. Indicators evaluated include knowledge and self-confidence score of health providers, in-hospital regulations, changes of asphyxia incidence and mortality. Results: Over 90% of intervention hospitals had carried out neonatal resuscitation related regulations requiring that trained paediatricians participate in case discussion of high-risk delivery and onsite resuscitation, while in control hospitals less than 55% had such requirements. The average knowledge score of health providers was significantly higher in the intervention counties than the control counties (9.19±1.18 VS 8.40±1.52). The average self-confidence score in the two groups were 57.33±2.50 and 54.09±8.19 respectively. The incidence of birth asphyxia (defined as Apgar score≤7) decreased from 8.83% to 5.99% in the intervention counties, and the intrapartum-related deaths in the delivery room decreased from 27.60 to 5.03 per 100, 000. No significantly changes were found in the control counties. Conclusions: Setting up long-term mechanism of neonatal resuscitation training is an effective method to strengthen in-hospital training, build up capability for neonatal resuscitation and therefore, can decrease the incidence of neonatal asphyxia.